PENGARUH KOMPETENSI PROFESIONAL GURU TERHADAP MINAT BELAJAR PESERTA DIDIK PADA PELAJARAN FISIKA DI SMPN 3 TONDANO - Wenda, Yes; Palilingan, Rolles Nixon; Tumimomor, Farly Reynol (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
Teachers' professional competence refers to their ability to master learning materials comprehensively and in-depth, enabling them to guide students in achieving the competency standards set by the national education system. This study aims to analyze the influence of teachers' professional competence on students' interest in learning Physics at SMP Negeri 3 Tondano. Data collection was conducted using observation, questionnaire, and documentation methods. The data analysis results indicate that the coefficient of determination is 0.4773, meaning that 47.73% of students' interest in learning is influenced by teachers' professional competence. Based on regression analysis, the equation Y=93.85+1.29X was obtained. Meanwhile, the remaining 52.27% of students' interest is influenced by other factors. Therefore, it can be concluded that there is a positive relationship between teachers' professional competence and students' interest in learning Physics.